2007
DOI: 10.2337/dc06-2375
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Once-Weekly Dosing of a Long-Acting Release Formulation of Exenatide on Glucose Control and Body Weight in Subjects With Type 2 Diabetes

Abstract: OBJECTIVE -In patients with type 2 diabetes, exenatide reduces A1C, postprandial and fasting glucose, and weight. In this study we investigated the effects of continuous exenatide administration from a long-acting release (LAR) formulation.RESEARCH DESIGN AND METHODS -In this randomized, placebo-controlled phase 2 study, exenatide LAR (0.8 or 2.0 mg) was administered subcutaneously once weekly for 15 weeks to subjects with type 2 diabetes (n ϭ 45) suboptimally controlled with metformin (60%) and/or diet and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
337
3
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 417 publications
(363 citation statements)
references
References 28 publications
16
337
3
7
Order By: Relevance
“…Weekly exenatide administration led to clinically significant improvements in glycaemic control that were evident by week 4, and steady‐state concentration of exenatide at approximately week 8 was consistent with previous studies 16, 17, 18, 19. Continuous exposure of exenatide translated into similar glucose‐lowering effects at the beginning and end of the week.…”
Section: Discussionsupporting
confidence: 87%
“…Weekly exenatide administration led to clinically significant improvements in glycaemic control that were evident by week 4, and steady‐state concentration of exenatide at approximately week 8 was consistent with previous studies 16, 17, 18, 19. Continuous exposure of exenatide translated into similar glucose‐lowering effects at the beginning and end of the week.…”
Section: Discussionsupporting
confidence: 87%
“…A second study comparing a 16-vs. 24-h GLP-1 infusion in patients indicated that greater efficacy could be achieved with sustained 24-h coverage (38), with no evidence of tachyphylaxis or loss of activity. Finally, treatment with exendin-LAR has been reported to reduce A1C as much as 2% in the high-dose group (39). Since the half-life for exendin-LAR was reported to be 14 -15 days, the data confirms that sustained exposure to a GLP-1 analogue has potential for profound efficacy.…”
Section: Fig 5 Cnto736 Is Present In the Area Of The Hypothalamus Amentioning
confidence: 56%
“…As seen consistently in previous studies [6,7,11,13,14], vildagliptin was weight-neutral. Although vildagliptin is thought to act primarily through increasing plasma levels of the active form of GLP-1 and GLP-1 agonists can lead to substantial weight loss [20], the degree of GLP-1 receptor signalling induced by the more physiological levels of GLP-1 achieved with vildagliptin may underlie the lack of weight gain but be insufficient to elicit significant weight loss.…”
Section: Discussionmentioning
confidence: 99%